Amniotic membrane transplantation for infectious corneal ulcer treatment: a cohort retrospective study (Medical Journal of Indonesia, 2020)
BACKGROUND Corneal ulcer is one of the most common causes of corneal blindness. This study aimed to describe the outcomes of amniotic membrane transplantation (AMT) in patients with infectious corneal ulcer. METHODS A retrospective cohort study based on medical records of patients who underwent an adjuvant AMT procedure over a 2-year period (2015–2017) was conducted at Cipto Mangunkusumo Hospital Jakarta. Uncorrected visual acuity (UCVA) was measured with the Snellen chart. Treatment success was marked by complete healing (disappearance of corneal infiltrates, epithelial defect closure, and corneal scar formation). Healing time was the duration from AMT surgery to complete healing. RESULTS 50 cases of infectious corneal ulcer, 12 of which had perforation were included. Gram-positive cocci (18%), gram-negative rods (14%), fungi (4%), and Acanthamoeba (2%) were isolated from culture specimens. Successful results were observed in 90% of cases (20/21 moderate cases and 25/29 severe cases). Healing time was 21 (14–63) days in moderate cases and 28 (14–90) days in severe cases. Baseline UCVA improved from 2.48 (0.22–2.80) logMAR to 1.30 (0–2.80) logMAR within 3–4 weeks postoperatively and to 0.94 (0–2.80) logMAR at the last follow-up. Post-AMT complications included recurrent perforation in 4 eyes, persistent epithelial defects in 2 eyes, amniotic membrane infection in 1 eye, and membrane retraction in 1 eye. CONCLUSIONS AMT was successfully used to treat moderate and severe infectious corneal ulcer, particularly in nonresponsive and some perforated cases. AMT provides biochemical and mechanical support for corneal wound healing with good visual outcomes.